Jornadas interdisciplinares: do mito de Quíron à construção da metáfora da cura na escola - Souza, Fernando César de (2009)
This paper describes some interdisciplinary research, with groups of teachers from public and private school aiming the development of the metaphor of healing in research spaces called in loco during what we can call journeys. The central focus is to expand the meaning of the word cure as care into two categories: caring for oneself and care for others, reaching a dialogue born in Education and commixture with the philosophical and medical fields. It is entering into seemingly unrelated areas such as school or medical clinic, not necessarily act as a health professional, or a function of a religious person (nun Zen Buddhist; Catholic nun) or philosopher in training, public school teacher. Tracks and dialogues were recorded with various professionals who live the paradox disease & healing within or outside the school, ushered in a different methodological approach to envolve in action that which seeks the key to navigate through the mythical, philosophical and scientific biases. The stories, experiences and testimonies were theoretically served as the basis of the principles of the Brazilian Interdisciplinary and Jungian Symbolic Education presented in each journey, in the conflicts and contradictions inherent, in the ongoing process of teaching-learning, in different master-apprentice relationships to gain understanding that to teach is caring for others and self-care. It was found that the readings of the meanings that emerge from the school routine is not discussed the question of the medicinal cure directly, there is an ingratiating mind / body healing arising from the entirety of the journey whose the utilization of metaphor offered possibilities to envision the relationship of knowledge, of doing, being and now ... of care